2015
DOI: 10.1371/journal.pone.0144916
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cycling Performance: Transcranial Direct Current Stimulation Increases Time to Exhaustion in Cycling

Abstract: The central nervous system seems to have an important role in fatigue and exercise tolerance. Novel noninvasive techniques of neuromodulation can provide insights on the relationship between brain function and exercise performance. The purpose of this study was to determine the effects of transcranial direct current stimulation (tDCS) on physical performance and physiological and perceptual variables with regard to fatigue and exercise tolerance. Eleven physically active subjects participated in an incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
171
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(190 citation statements)
references
References 27 publications
8
171
4
1
Order By: Relevance
“…To the best of our knowledge only four studies have previously investigated the effects of tDCS on various measures of endurance performance [1719,21]. In a previous study from our laboratory, we found no significant changes in TTF during cycling exercise when a cephalic montage was administered with a single anodal electrode over one M1 and with the cathode over contralateral prefrontal cortex [21].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To the best of our knowledge only four studies have previously investigated the effects of tDCS on various measures of endurance performance [1719,21]. In a previous study from our laboratory, we found no significant changes in TTF during cycling exercise when a cephalic montage was administered with a single anodal electrode over one M1 and with the cathode over contralateral prefrontal cortex [21].…”
Section: Discussionmentioning
confidence: 84%
“…With specific reference to the enhancement of endurance performance, the acute administration of anodal stimulation over the contralateral primary motor cortex (M1) prior to or during isometric time to task failure (TTF) tests of isolated muscle groups has induced either an improvement [1013], or no effect [14,15]. A similar inconsistency in endurance performance outcomes has been also reported in cycling studies [1619]. The inconsistent effects of tDCS on endurance performance found in previous experimental studies might be partly caused by the different electrode montages adopted [20].…”
Section: Introductionmentioning
confidence: 89%
“…Recent research investigating the effects of tcDCS on steady state cycling endurance found that anodal stimulation attenuated central fatigue mechanisms and allowed cyclists to increase their time to exhaustion [31]. Similar to the effects of tcDCS on supraspinal fatigue mechanisms, it appears that anodal tsDCS interferes with the regulatory actions that spinal circuits have on motor unit excitability and eccentric contraction fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond NFB training, there are other methods to improve skills and motor performance based on neuroplasticity 38,39,40 . Non-invasive brain stimulation (NIBS) techniques facilitate motor skill learning by increasing the corticospinal excitability.…”
Section: Psychophysiological Interventions: Bio-neurofeedback and Tramentioning
confidence: 99%